Gaps in students' performance in PISA: What explains Colombia's difference from Finland and Chile? - Luz Karime Abadia; Gloria Lucia Bernal; Santiago Muñoz (Arizona State University, 2018)
Historically Colombia has performed poorly in the PISA tests, whereas Chile has the best performance of Latin America and Finland is usually within the first places in the world. Using the methodology of DiNardo, Fortin and Lemieux (1996), we construct counterfactual scenarios where Colombian students hypothetically assume the distribution of Finnish or Chilean students and evaluate its relative impact on scores. The results confirm that if Colombian students have had the distribution of family background characteristics of Finnish or Chilean students, their academic achievement would have been higher. Among this component, the proxy wealth of households has the greater impact to explain the gap. Moreover, among the set of analyzed factors, the intrinsic variables-such as attitude and motivation of students for learning-become important to explain the differences in academic performance in comparison to Finland, whereas the school characteristics in the case of Chile explain the greater proportion of the gap. The results present heterogeneous magnitudes of the determinants along the scores distribution.